A novel gelatin crosslinking method retards release of mulberry 1-deoxynojirimycin providing a prolonged hypoglycaemic effect - Vichasilp C. (2014)
Mulberry 1-deoxynojirimycin (DNJ), a potent α-glycosidase inhibitor, has therapeutic potency in the suppression of postprandial blood glucose levels thereby possibly preventing diabetes mellitus. However, DNJ has a relatively short half-life in vivo (about 2 h). Therefore, several doses of mulberry DNJ are required to achieve optimal therapeutic results. This study aimed to delay the release of mulberry DNJ with biodegradable matrices to maintain the intestinal DNJ concentration and prolong the hypoglycaemic effect in vivo. A novel, simple, and commercially viable method was adopted to develop DNJ-entrapped microspheres (DNJ-MSs). A higher extent of crosslinking and the larger sized DNJ-MS decreased the rate of mulberry DNJ release in vitro. Consequently, an in vivo study was performed in Wistar rats over a 6 h period. The area under curve (AUC) of rats with DNJ-MS was significantly increased, compared to animals dosed with mulberry powder (control). DNJ-MS suppressed postprandial glucose from sucrose administration at the initial and 3 h time points indicating a prolonged hypoglycaemic effect. © 2012 Elsevier Ltd. All rights reserved.